Rational water use in Egypt - Abdin A.E.; Gaafar I. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
In Egypt, the pressures on the country's water resources are alarming as Egypt depends on a single source of water which is the Nile River. Demand-oriented measures that can be implemented in Egypt include: i) shifting to less water-demanding crops, ii) improving the efficiency of the existing public water supply system, iii) introducing tariffs for water conservation and iv) launching public awareness campaigns aimed at advocating a new water culture in a society based on the principle of conservation. A number of measures towards the rational use of water are already applied but still need extra efforts to be fully successful. Enhancing the institutional organizations, involving the private sector, stringent laws and cooperation with the Nile Countries are considered a must to increase the water use efficiency, control water demand and reduce the over irrigation and the misuse of water. Optimum use of water resources is implemented through the reuse of drainage water, recycling the domestic and industrial wastewater and desalination. Co-operation with the riparian countries of the Nile Basin is expected to implement Upper Nile Projects and in return to lead to additional inflow into Lake Nasser. This paper can be considered as an attempt towards highlighting the ways and means for a rational use of water so as to improve water use efficiency in Egypt. Emphasis will be laid on how to utilize the available quantity of water as well as how to get additional quota for Egypt through the Nile Basin Initiative projects.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)